Dysbiosis of Skin Microbiota in Psoriatic Patients: Co-occurrence of Fungal and Bacterial Communities - Stehlikova, Zuzana; Kostovcik, Martin; Kostovcikova, Klara; Kverka, Miloslav; Juzlova, Katerina; Rob, Filip; Hercogova, Jana; Bohac, Petr; Pinto, Yishay; Uzan, Atara; Koren, Omry; Tlaskalova-Hogenova, Helena; et al. (Frontiers in Microbiology, 2019)
Psoriasis is a chronic inflammatory skin disease, whose pathogenesis involves dysregulated interplay among immune cells, keratinocytes and environmental triggers, including microbiota. Bacterial and fungal dysbiosis has been recently associated with several chronic immune mediated diseases including psoriasis. In this comprehensive study, we investigated how different sampling sites and methods reflect the uncovered skin microbiota composition. After establishing the most suitable approach, we further examined correlations between bacteria and fungi on the psoriatic skin. We compared microbiota composition determined in the same sample by sequencing two distinct hypervariable regions of the 16S rRNA gene. We showed that using the V3V4 region led to higher species richness and evenness than using the V1V2 region. In particular, genera such as Staphylococcus and Micrococcus were more abundant when using the V3V4 region, while Planococcaceae, on the other hand, were detected only by the V1V2 region. We performed a detailed analysis of skin microbiota composition of psoriatic lesions, unaffected psoriatic skin, and healthy control skin from the back and elbow. Only a few discriminative features were uncovered, mostly specific for the sampling site or method (swab, scraping, or biopsy). Swabs from psoriatic lesions on the back and the elbow were associated with increased abundance of Brevibacterium and Kocuria palustris and Gordonia, respectively. In the same samples from psoriatic lesions, we found a significantly higher abundance of the fungus Malassezia restricta on the back, while Malassezia sympodialis dominated the elbow mycobiota. In psoriatic elbow skin, we found significant correlation between occurrence of Kocuria, Lactobacillus and Streptococcus with Saccharomyces, which was not observed in healthy skin. For the first time, we showed here a psoriasis-specific correlation between fungal and bacterial species, suggesting a link between competition for niche occupancy and psoriasis. However, it still remains to be elucidated whether observed microbial shift and specific inter-kingdom relationship pattern are of primary etiological significance or secondary to the disease.